Reaksi Esensial Oil Lavender Pada Recovery Denyut Jantung Atlet Bolavoli - Edi Irwanto; Arik Winarto (Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
Aromatherapy is a therapeutic action using essential oils that are useful for improving a person's physical and psychological state to become better, one of which is by using lavender essential oil. The purpose of this study was to determine the reaction of giving lavender essential oil on decreasing the pulse rate of UNIBAVC volleyball players. The method used in this study is an experimental method of one group pretest-posttest design with a sample of 10 players. The research instrument uses the measurement of the exercise pulse and initial pulse rate in athletes. The tools and materials used include lavender essential oil, Fingertip Pulse Oximeter, Stopowatch. Analysis was carried out by calculating the T test.The results showed that the use of lavender essential oil by applying it on the chest could accelerate the recovery of the pulse rate of UNIBAVC volleyball players with a significance value of 4.49.The conclusion of this study is that the use of lavender oil can be an alternative used during matches to speed up the recovery process for athletes, especially volleyball athletes